HISTOMORPHOMETRIC STUDY OF EPITHELIAL LAYER OF HUMAN SPHENOIDAL SINUS MUCOSA - Sovhyria, S.M. (World of Medicine and Biology, 2019)
Peculiarities of the morphological structure of the mucous membrane of the nasal cavity and paranasal sinuses should be considered while performing functional endoscopic interventions on the paranasal sinuses. To avoid the majority of pathomorphological errors, a diagnostician must be an expert in the morphological features of the study material. Therefore, a qualitative biopsy diagnostics requires detailing on the structure of the mucous membrane of different walls of the human normal sphenoidal sinus mucosa. The present study histomorphologically evaluated the homogeneity of the cellular composition of the pseudostratified ciliated columnar epithelium of the mucous membrane, lining the different walls of the human sphenoidal sinus mucosa. It has been found that each wall has its cytological picture, which in our opinion depends on certain functional purpose.
Keywords: sphenoidal sinus; mucous membrane; ciliated epithelium